Raba avgmentiranih preteklih glagolskih časov v stari indijščini - Terbovšek Coklin, Nataša (Slavistična revija, 2007)
The article attempts to illuminate from one perspective a poorly understood issue of the sytac of the Old Indian verb. The author shows various methods of use of Vedic and classical augmented verbal tenses and analyzes the functional difference between them, i.e., the difference between the use of the imperfect abd the aorist with respect to their indicative meaning, as is found in the main works of classical literature and in the Rigveda.
Keywords: aorist; classical Old Indian; glagol; glagolski čas; imperfect; imperfekt; klasična stara indijščina; past verbal tenses; pretekli čas; tense; Vedic Old Indian; vedska stara indijščina; verb